Bilateral Cleft Lip and Palate, With Facial Dysplasia: Interdisciplinary Treatment and Long-Term Follow-Up. Issue 6 (September 2018) - Bennun, Ricardo D.; Harfin, Julia H.
Abstract : Abstract: Bilateral complete clefts represent the result of an incomplete fusion with all the morphologic components present. It is well known that patients with bilateral cleft lip and palate have typical characteristics such as insufficient medial face development with an orthodontic class III tendency, flat nose and short columella with abnormal nasolabial angle, bilateral oronasal fistulas, alterations in the number and position of the lateral incisors, and agenesis or supernumerary teeth. Successfully solving these cases, results in a difficult challenge and studies showing extended follow-up are not frequent. Bilateral complete clefts, including medial facial dysplasia, are a rare condition, not only difficult to be included in any classification but also of complex solution. These patients require multiple surgical procedures throughout life, and long-term results are often still far from ideal. Due to surgical intervention and diminished intrinsic growth potential, surgical results may change from initially good into a progressively disappointing outcome. However, if the ideal timing and type of surgery are known, in combination with the intrinsic growth potential, these results could be ameliorated. A patient with complete bilateral cleft, presenting hypoplasia of philtrum and premaxilla, flat nose with rudimentary columella and septum, is reported. A description of her interdisciplinary treatment and long-term outcome with an adequate and stable result was observed. Being the intrinsic growth restriction mainly localized in the central mid-face, a protocol oriented to stimulate facial development during growth period could be essential to reduce the number of surgical procedures and prevent sequels. Early referral to a specialized center is mandatory to achieve a correct treatment and result.